2021
DOI: 10.1016/j.annonc.2021.08.516
|View full text |Cite
|
Sign up to set email alerts
|

233P Association of quality of life (QOL) with overall survival (OS) in patients (pts) with HR+/HER2− advanced breast cancer (ABC) treated with ribociclib (RIB) + endocrine therapy (ET) in the MONALEESA-3 (ML-3) and ML-7 trials

Abstract: Association of quality of life (QOL) with overall survival (OS) in patients (pts) with HR+/HER2L advanced breast cancer (ABC) treated with ribociclib (RIB) + endocrine therapy (ET) in the MONALEESA-3 (ML-3) and ML-7 trials

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
1
0
2
Order By: Relevance
“… 54 Consistently, a pooled analysis including the overall population of the MONALEESA-3 trial and patients treated with ribociclib/placebo plus an NSAI in the MONALEESA-7 trial demonstrated a greater GHS improvement in patients with longer overall survival, especially among subjects receiving ribociclib. 55 Another pooled analysis of HR-QoL results was conducted in the whole population of the MONALEESA-2 study, in patients receiving ribociclib plus fulvestrant or placebo plus fulvestrant as first-line treatment in the MONALEESA-3 trial and in patients treated with ribociclib/placebo plus an NSAI in the MONALEESA-7 trial. In line with the result of the single studies, GHS and QoL were maintained throughout the treatment period to decline at the time of study discontinuation in both arms, whereas TTD of GHS, pain and emotional functioning was delayed in the ribociclib group.…”
Section: Resultsmentioning
confidence: 99%
“… 54 Consistently, a pooled analysis including the overall population of the MONALEESA-3 trial and patients treated with ribociclib/placebo plus an NSAI in the MONALEESA-7 trial demonstrated a greater GHS improvement in patients with longer overall survival, especially among subjects receiving ribociclib. 55 Another pooled analysis of HR-QoL results was conducted in the whole population of the MONALEESA-2 study, in patients receiving ribociclib plus fulvestrant or placebo plus fulvestrant as first-line treatment in the MONALEESA-3 trial and in patients treated with ribociclib/placebo plus an NSAI in the MONALEESA-7 trial. In line with the result of the single studies, GHS and QoL were maintained throughout the treatment period to decline at the time of study discontinuation in both arms, whereas TTD of GHS, pain and emotional functioning was delayed in the ribociclib group.…”
Section: Resultsmentioning
confidence: 99%
“…Однако в 2021 г. P. Fasching и соавт. опубликовали данные о том, что улучшение качества жизни по опроснику EORTC QLQ-C30 прямо коррелировало с долей пациентов, у которых отмечена более длительная ОВ [39]. Принимая во внимание положительные результаты исследования эффективности рибоциклиба, важно рассмотреть и качество жизни на фоне терапии [40].…”
Section: качество жизниunclassified
“…Кроме того, усиление болевого синдрома, время до ухудшения эмоционального и социального функционирования по крайней мере на 10% при терапии рибоциклибом наступало позднее, чем на ГТ + плацебо. Авторы анализа делают вывод, что комбинированная терапия рибоциклибом и ГТ не только приводит к увеличению ОВ, но и значимо влияет на сохранение удовлетворительного качества жизни пациенток с люминальным HER2-отрицательным распространенным РМЖ [17].…”
Section: оценка качества жизни в клинических исследованиях Monaleesaunclassified